MEANING CONSTRUCTION BEHIND PUTERI INDONESIA BEAUTY PAGEANT’ SLOGAN: BRAIN, BEAUTY, AND BEHAVIOR - IRIANI, SAFANA PUTRI (Jurnal Ilmiah Mahasiswa FIB, 2013)
This study aimed at finding out; (1). the meaning constructions in the slogan ofKeywords: Critical Discourse Analysis, Slogan, Beauty pageant, Puteri Indonesia, Brain, Beauty, and BehaviorPuteri Indonesia beauty pageant “Brain, Beauty, and Behavior”, also (2). the social effects of the meaning constructions of 3Bs “Brain, Beauty, and Behavior” reflected on the image of Puteri Indonesia.This study uses qualitative approach. The writer conducted the study toward the construction meaning and the effect of the slogan Brain, Beauty, and Behavior according to the image of the winner of Puteri Indonesia beauty pageant produced in the articles. In analyzing the data found from the article, the researcher approached to several processes. Firstly, finding and selecting the articles related to Puteri Indonesia. Secondly, explaining textual analysis, discourse analysis, and also the social practice based on Norman Fairlough’s theory (2001) of Critical Discourse Analysis which then brings into the direct analysis to the social effect on the use of slogan Brain, Beauty, and Behavior” reflected on the image of Puteri Indonesia.This present study reveals that based on the textual analysis on the slogan, the use of the word Brain as the starting point has big impact towards the public opinion. It could influence public’s view to this pageant that it does not come out as a "stereotypical" pageant. The social effect on the using of slogan 3Bs for the winner can be seen in everyday life. The winner often gets many privileges in the society. The most recent phenomenon can be seen in Angelina Sondakh’s case. This former winner of Puteri Indonesia was accused in a graft case revolving around the high-profile SEA Games’ bribery case. However, a day before her court day she read a pledoi which contains all of her prestigious achievements. One of them is her title as the former winner of Puteri Indonesia that brought her to what she is now. In this case, her threat of punishment that used to be 20 years or life time sentence in prison becomes only 4.5 years in prison with 250 million of fine causing public to criticize the judge ’s decision.Finally, writer suggests for the future researcher to enrich the field of this study, by possibly exploring other numerous object with different theory for CDA. Moreover, it can be about CDA containing a critical thinking which in fact is very helpful for students to explore more about a subject given whether they will accept it or not. It can bring the students to have 'self actualization' and 'self evaluation’. 12